Secretion of RANTES and interleukin-8 by the human gastric epithelial cell line (MKN45) through modulation with cytokines - Norina Abdullah,; Jordon N.J,; Kolios G.,; Colloins A.J, (penerbit ukm, 2003)
In this vitro study, the secretion of interleukin-8 (IL-8) and RANTES proteins by the MKN45 gastric epithetial cell line was examined using the ELISA technique after the cells had been stimulated with pro-inflammatory cytokines, I,e,II, I "α" ,TNF-α and IFN-γ, The chemokines demonstrated a timedependent increase in concentration after stimulation with the various cytokines, alone or in combination, IL-I α was the weakest stimuli while a combination of IL-I α, TNF-α and IFN-γ provided the strongest stimulation. The immunomodulatory effects of IL-4 and IL-13 on the chemokine protein secretion were also studied. Stimulation of the cells with IL-4 and IL-13 for an hour at relatively high concentrations (10 and 30 ng/ml) prior to stimulation with the combination of IL-I α, TNF-α and IFN –γ inhibited the secretion of RANTES protein but did not inhibit the secretion of IL-8 mRNA of protwin. This inplied that the chemokines might have different inbitiory pathways. IL-4 and IL-13 played an important role in decreasing certain inflammatory chemokines and this might have an important effect in decreasing gastric inflammation.